Abcg2a is the functional homolog of human ABCG2 expressed at the zebrafish blood–brain barrier - Joanna R. Thomas; William J. E. Frye; Robert W. Robey; Andrew C. Warner; Donna Butcher; Jennifer L. Matta; Tamara C. Morgan; Elijah F. Edmondson; Paula B. Salazar; Suresh V. Ambudkar; Michael M. Gottesman (Fluids and Barriers of the CNS)
Abstract Background A principal protective component of the mammalian blood–brain barrier (BBB) is the high expression of the multidrug efflux transporters P-glycoprotein (P-gp, encoded by ABCB1) and ABCG2 (encoded by ABCG2) on the lumenal surface of endothelial cells. The zebrafish P-gp homolog Abcb4 is expressed at the BBB and phenocopies human P-gp. Comparatively little is known about the four zebrafish homologs of the human ABCG2 gene: abcg2a, abcg2b, abcg2c, and abcg2d. Here we report the functional characterization and brain tissue distribution of zebrafish ABCG2 homologs. Methods To determine substrates of the transporters, we stably expressed each in HEK-293 cells and performed cytotoxicity and fluorescent efflux assays with known ABCG2 substrates. To assess the expression of transporter homologs, we used a combination of RNAscope in situ hybridization probes and immunohistochemistry to stain paraffin-embedded sections of adult and larval zebrafish. Results We found Abcg2a had the greatest substrate overlap with ABCG2, and Abcg2d appeared to be the least functionally similar. We identified abcg2a as the only homolog expressed at the adult and larval zebrafish BBB, based on its localization to claudin-5 positive brain vasculature. Conclusions These results demonstrate the conserved function of zebrafish Abcg2a and suggest that zebrafish may be an appropriate model organism for studying the role of ABCG2 at the BBB.